2019
DOI: 10.3390/electronics8070758
|View full text |Cite
|
Sign up to set email alerts
|

Throughput Enhancement in Downlink MU-MIMO Using Multiple Dimensions

Abstract: This paper focuses on the throughput performance enhancement in the single cell multi-user MIMO (MU-MIMO) downlink system model. For better quality of service, this paper proposes the scheme that increases system throughput and improves the spectral efficiency. Specifically, the signal transmission and detection schemes are proposed by using multiple dimensions. At the transmitter side, two dimensions (power and space) are adopted at the same time. To achieve multiple access (MA), the space domain is exploited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Its optimization criteria is to maximize the minimum uplink signal-to-interference plus noise power ratio (SINR). Efficient channel state information (CSI) estimation scheme was proposed in [13]. It exploits prior CSI of the previous timeslot having temporal correlation in the angular domain.…”
Section: The Present Issuementioning
confidence: 99%
“…Its optimization criteria is to maximize the minimum uplink signal-to-interference plus noise power ratio (SINR). Efficient channel state information (CSI) estimation scheme was proposed in [13]. It exploits prior CSI of the previous timeslot having temporal correlation in the angular domain.…”
Section: The Present Issuementioning
confidence: 99%
“…A review of modern publications devoted to MIMO modelling [6,7,[12][13][14] showed that scientists prefer to describe such systems at the physical level with the implementation of an electromagnetic approach to modelling a MIMO transmission channel. In most cases, the functioning of multiantenna communication systems is modelled using the equivalent representation of the latter in the form of multipoles [14][15][16][17]. In the basis of this approach, the transmitting part (signal generators, transmitting devices, matching devices), the receiving part (receiving devices, matching devices, payloads) and the communication channel (signal propagation medium, transmitting and receiving antennas) are represented by equivalent multipoles and are described by the corresponding parametric matrices.…”
Section: Introductionmentioning
confidence: 99%
“…In the future, studies aim to increase channel capacity in the overall wireless communication systems in order to handle explosive data traffic [1]. Multiple-input multiple-output (MIMO) technology has been studied in the wireless communication systems since tremendous increase of channel capacity is implemented [2][3][4][5][6][7]. In the MIMO systems, accurate signal detection is one of the main issues and various researches for the MIMO detection have been proposed for efficient signal detection [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%